Behavior of Halal Cosmetic Product Purchase Decision In Generation Z - Afendi, Arif; Mashilal, Mashilal; Ghofur, Abdul; Izza, Nabilla Baitul (Journal of Digital Marketing and Halal Industry, 2024)
One of the halal lifestyles that continues to increase in Indonesia is the use of halal cosmetic products. The purpose of this study was to examine the effect of religiosity and country of origin on purchase decisions for halal cosmetic products through the variable halal awareness as an intervening variable. Analysis of the model used is Partial Least Square-Structural Equation Modeling (PLS-SEM). The data in this study are primary data with 273 generation Z respondents in Central Java Province who use halal cosmetic products. The sampling technique was carried out using purposive sampling method. The results showed that there was a positive and significant influence between religiosity and country of origin on purchase decisions for halal cosmetic products. Furthermore, halal awareness is able to mediate the relationship between religiosity and country of origin on the decision to purchase halal cosmetic products. Policy implications that can be applied by stakeholders include increasing halal education policies, strengthening halal certification on imported cosmetic products, facilitating halal certification on MSME products, and helping to promote local halal cosmetic products.